Obesity and its association with comorbidities and hospital charges among patients hospitalized for dental conditions. Issue 3 (9th January 2015) - Allareddy, Veerasathpurush; Rampa, Sankeerth; Anamali, Sindhura; Lee, Min Kyeong; Allareddy, Veerajalandhar; Nalliah, Romesh P.
Abstract: Aim: The aim of the present study was to examine the impact of obesity on hospitalization charges and comorbid burden following hospitalization due to dental conditions. Methods: The Nationwide Inpatient Sample for 2004–2010 was used. All hospitalizations due to dental conditions were selected. The prevalence of obesity was estimated among these hospitalizations. Multivariable linear regression models were used to examine the impact of obesity on outcomes. Results: A total of 11 965 hospitalizations were attributed to dental conditions; 5.6% were related to obesity. The proportion of those who were obese increased over the study period (ranging from 3.7% in 2004 to 7.3% in 2010). The mean age of those who were obese was 45 years (compared to 38.7 years for those who were not obese). Close to 41% of those who were obese were males (compared to 51% who were not obese). Whites comprised 62.4% of those who were obese (compared to 59.2% of those who were not obese). Those who were obese had a higher comorbid burden compared to those who were not obese (83.5% of those who were obese had at least one comorbid condition, whereas 56.4% of those who were not obese had at least one comorbid condition). Those who were obese had higher hospitalization charges ($US2225 more, P  =   0.0001). Conclusions: Obesity is associated with high comorbid burden and hospital charges among patients hospitalized due to dental conditions.